2016
DOI: 10.1158/0008-5472.can-15-1798
|View full text |Cite
|
Sign up to set email alerts
|

Lack ofp53Augments Antitumor Functions in Cytolytic T Cells

Abstract: Repetitive stimulation of T cell receptor (TCR) with cognate antigen results in robust proliferation and expansion of the T cells, and also imprints them with replicative senescence signatures. Our previous studies have shown that life-span and anti-tumor function of T cells can be enhanced by inhibiting reactive oxygen species (ROS) or intervening with ROS dependent JNK activation that leads to its activation induced cell death (AICD). Since tumor suppressor protein p53 is also a redox active transcription fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…Data are presented as the ratio (fold-change) between MFI (Median fluorescence intensity) of H3K9me2 CD8+ T cells detected in treated vs. untreated cultures from individual patients; statistical analysis was performed with the Wilcoxon signed-rank test; columns and dots represent median values and single patients, respectively. relevance of our model to other T cell exhaustion-associated pathologies, including cancer, is further corroborated by the increased effector function and enhanced glycolytic commitment exhibited by T cells derived from p53 knock-out mice 53 . In the same model, adoptive transfer of p53 knock-out T cells has been shown to improve the control of a subcutaneously established murine melanoma, thus highlighting a key role of p53 in modulating tumor-reactive T-cell responses with a potential translational significance in adoptive T-cell therapy 53 .…”
Section: Discussionsupporting
confidence: 53%
“…Data are presented as the ratio (fold-change) between MFI (Median fluorescence intensity) of H3K9me2 CD8+ T cells detected in treated vs. untreated cultures from individual patients; statistical analysis was performed with the Wilcoxon signed-rank test; columns and dots represent median values and single patients, respectively. relevance of our model to other T cell exhaustion-associated pathologies, including cancer, is further corroborated by the increased effector function and enhanced glycolytic commitment exhibited by T cells derived from p53 knock-out mice 53 . In the same model, adoptive transfer of p53 knock-out T cells has been shown to improve the control of a subcutaneously established murine melanoma, thus highlighting a key role of p53 in modulating tumor-reactive T-cell responses with a potential translational significance in adoptive T-cell therapy 53 .…”
Section: Discussionsupporting
confidence: 53%
“…The pharmacological inhibition of p53 can protect activated T cells from death following TCR restimulation (11), and we have recently demonstrated that T cells from p53-knockout mice are likewise protected from AICD (26). However, the activation status of p53 has not previously been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, enhanced growth of tumours in p53-null hosts is likely to reflect, to some extent, the consequences of loss of p53 in the immune cells. Therefore, in order to dissect the role of p53 in various immune compartments, genetic alterations of p53 in monocytes, pan myeloid lineages and T cells have been investigated (Banerjee et al, 2016;He et al, 2015;Sharma et al, 2018) (Fig. 4).…”
Section: Alterations Of P53 In Leukocytes Affect Tumour Growthmentioning
confidence: 99%
“…4). Furthermore, genetic deletion of p53 in antigen-specific T cells increases their metabolic fitness and reduces human melanoma growth in xenograft models (Banerjee et al, 2016) (Fig. 4).…”
Section: Alterations Of P53 In Leukocytes Affect Tumour Growthmentioning
confidence: 99%